2006
DOI: 10.1371/journal.pgen.0020171
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of Intergenic Transcription: An Evolutionary Comparison

Abstract: Although a large proportion of human transcription occurs outside the boundaries of known genes, the functional significance of this transcription remains unknown. We have compared the expression patterns of known genes as well as intergenic transcripts within the ENCODE regions between humans and chimpanzees in brain, heart, testis, and lymphoblastoid cell lines. We find that intergenic transcripts show patterns of tissue-specific conservation of their expression, which are comparable to exonic transcripts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 23 publications
(46 reference statements)
7
62
0
2
Order By: Relevance
“…These findings are consistent with an earlier study that showed conserved tissue-specific intergenic transcription between human and chimpanzee in brain, heart, and testis (Khaitovich et al 2006). Conservation of tissue specificity of lincRNAs might be an indirect effect through coregulation with mRNAs.…”
Section: Conservation Of Lincrna Tissue Specificitysupporting
confidence: 93%
“…These findings are consistent with an earlier study that showed conserved tissue-specific intergenic transcription between human and chimpanzee in brain, heart, and testis (Khaitovich et al 2006). Conservation of tissue specificity of lincRNAs might be an indirect effect through coregulation with mRNAs.…”
Section: Conservation Of Lincrna Tissue Specificitysupporting
confidence: 93%
“…[28][29][30] Similarly, by whole chromosome RNA analysis it has been observed that about 93% of the human genome sequence is pervasively transcribed in one or the other cell type. [31][32][33][34][35] Maximum of these transcripts are logically expected to be the "dark matter" of the genome or ncRNAs of diverse biological functions. 36 Recently, a class of small regulatory RNAs called piRNAs (PIWI-interacting RNAs) have been reported to function for silencing of transposons in the germline.…”
Section: Long Interspersed Nuclear Elements (Lines)mentioning
confidence: 99%
“…Nevertheless, their expression patterns may be conserved among tissues or along developmental axes. 14,15 More importantly, ncRNA function in gene regulation has emerged as an important mechanism in the control of many biologic processes in development and carcinogenesis. 16 In the present study, we have identified intergenic transcription of a unique long ncRNA, here termed HOTAIRM1 (HOTAIR myeloid 1) after the nomenclature of Rinn et al, 7 located between the human HOXA1 and HOXA2 genes.…”
Section: Introductionmentioning
confidence: 99%